Association of Waist and Hip Ratio with the Angiographic Severity of Coronary Artery Disease in Patients with Non ST Segment Elevation Myocardial Infarction (Bangladesh Heart Journal, 2022)
Background: Obesity is a proven independent risk factor for coronary artery disease. There are different Methods for evaluation of obesity. The aim of this study is to evaluate the association between waist hip ratio and the severity of CAD in non-ST-segment elevation myocardial infarction patients.Methods: This cross-sectional observational study was done at the National Institute of Cardiovascular Diseases (NICVD), Dhaka. A total of 100 patients with NSTEMI who underwent coronary angiogram during the indexed hospitalization period were included in this study. On the basis of WHR, study patients were divided into two groups 50 patients of NSTEMI with normal WHR (Male